Respuesta :

frika

Answer:

C

Step-by-step explanation:

Angle Addition Postulate describes that putting two angles side by side with their vertices together creates a new angle whose measure equals the sum of the measures of the two original angles.

By Angle Addition Postulate,

[tex]m\angle LKJ=m\angle LKE+m\angle EKJ[/tex]

Since

[tex]m\angle LKJ = 153^{\circ}\\ \\m\angle LKE = (x + 36)^{\circ}\\ \\m\angle EKJ = (x + 105)^{\circ},[/tex]

you have

[tex]153^{\circ}=(x+36)^{\circ}+(x+105)^{\circ}\\ \\x+36+x+105=153\\ \\2x+141=153\\ \\2x=153-141\\ \\2x=12\\ \\x=6[/tex]

Answer:

C x=6

Step-by-step explanation:

m∠LKE + m∠EKJ = m∠LKJ → (x + 36) + (x + 105) = 153 → x = 6